Evaluasi Usability Aplikasi Mobile Ojek Indralaya (Ojin) Mengunakan System Usability Scale - Aldy Wiranata; Winoto Chandra (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The Indralaya Ojek (OJIN) application is one of the online motorcycle taxi applications in Indralaya, South Sumatra. OJIN is a transportation provider application that offers several services. These services are transportation services, courier services, and food delivery services. OJIN application is growing rapidly so that it has been downloaded more than 10 thousand times. Although it has been downloaded more than 10 thousand times, it is necessary to explore more comprehensive problems in order to explore the problems that occur in OJIN application users. It should also be noted how far the usability level of the OJIN application is. The usability level needs to be known to explain what level the usability of the OJIN application is at from the user's point of view. This study provides evaluation results to determine the level of usability that exists in the OJIN application using the system usability scale (SUS) method. The research method used is data analysis with the usability scale (SUS) system in which this study uses a quantitative approach, by distributing questionnaires conducted online and offline. Keywords— online motorcycle taxi application, OJIN, usability scale system